How connected are Chinese farmers to retail markets?: new evidence of price transmission - Liu, B.; Keyzer, M.; Boom, B. van den; Zikhali, Precious (Elsevier, 2012)
This paper examines the extent to which Chinese farmers are connected to regional agricultural markets by looking at the intensity of price transmission from retail markets to the farmgate. This intensity is indicative of the extent to which farmers might benefit from improved marketing opportunities and be exposed to price risks. We estimate the elasticity of farmgate prices to retail prices using price data for 170 markets, in 29 out of 33 provinces of China, at the detail of 12 main products and for the five-year period 1996 to 2000. In each province we find strong linkages between retail and farmgate prices with elasticities ranging between 0.6 and 1 and intensifying over time. This suggests that Chinese farmers are generally well connected to retail markets and that this connectivity has strengthened in the period considered, creating not only new opportunities but also new risks. It is also found that linkages are relatively weak in inland provinces, which is a point of concern in view of Chinese policies to create equal opportunities and equitable growth.